Geology and inclusion studies on the genesis of the Baolun gold deposit in Hainan Province, South China. Issue 4 (16th July 2020) - Yu, Liangliang; Xu, Deru; Chen, Weixin; Zhang, Bo; Tian, Lihui; Shan, Qiang
Abstract: The late Triassic Baolun gold deposit hosted by Silurian phyllites is a large‐scale high‐grade gold deposit in Hainan Island, South China. The ores can be classified into quartz‐vein dominated type and less altered rock type. Three mineralization stages were recognized by mineral assemblages. The early stage, as the most important mineralization stage, is characterized by a quartz–native gold assemblage. The muscovite−quartz−pyrite−native gold assemblage is related to the intermedium mineralization stage. In late mineralization stage, native gold and Bi‐bearing minerals are paragenetic minerals. Microthermometry analyses show that the early mineralization stage is characterized by two types of fluid inclusions, including CO2 ‐rich inclusions (C‐type) and aqueous inclusions (W‐type). C‐type inclusions homogenize at 276–335°C with an averaged value of 306°C and have salinities of 1.0–10.0 wt% NaCl equivalent (mean value of 4.9 wt% NaCl equivalent). W‐type inclusions homogenize at 252–301°C (mean value of 278°C) with salinity of 4.0–9.7 wt% NaCl equivalent (mean value of 7.4 wt% NaCl equivalent). In intermedium mineralization stage, C‐type and W‐type inclusions homogenize at 228–320°C (mean value of 283°C) and 178–296°C (mean value of 241°C), with salinities of 2.4–9.9 wt% NaCl equivalent (mean value of 6.5 wt% NaCl equivalent) and 3.7–11.7 wt% NaCl equivalent (mean value of 7.7 wt% NaCl equivalent), respectively. No suitable mineral, such as quartz or calcite, was found for fluid inclusion study from late mineralization stage. In contrast, only aqueous inclusions were found from post‐ore barren veins, which yielded lower homogenization temperatures ranging from 168–241°C (mean value of 195°C) and similar salinities (2.6–12.6 wt% NaCl equivalent with averaged value of 7.2 wt% NaCl equivalent). The different homogenization temperatures and similar salinities of C‐type and W‐type from each mineralization stage indicate that fluid immiscibility and boiling occurred. The Baolun gold deposit was precipitated from a CO2 ‐bearing mesothermal fluid, and formed at a syn‐collision environment following the closure of the Paleo‐Tethys.